Photocatalytic Degradation of Rhodamine-B by Ni/Zn LDH Intercalated Polyoxometalate Compound - Yulizah Hanifah; Risfidian Mohadi; Mardiyanto; Aldes Lesbani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
NiAl-LDH and ZnAl-LDH intercalated polyoxometalate K4 [SiW12O40] and K3 [PW12O40] were synthesized to form composite NiAl-[SiW12O40], NiAl-[PW12O40], ZnAl-[SiW12O40], and ZnAl-[PW12O40]. The physicochemical properties of the materials were characterized by XRD, FTIR, SEM, and UV-DRS. The material used for degraded Rhodamine B (RhB) as a cation dye. The results successfully synthesized by showed the peak diffractions angles at 11.63°, 23.13°, and 35.16° for NiAl-LDH and diffractions at 10.39°, 20.17°, 34.6° and 60.52°for ZnAl-LDH. The LDH typical structure of the composite materials NiAl-[SiW12O40] and NiAl-[PW12O40] was demonstrated by apparent diffraction at 2???? angles of 10.76°, 26.59°, 30.8°, and 63.11° for NiAl [PW12O40], 2???? angles at 8.26°, 11.34°, 29°, and 35.1° for NiAl-[SiW12O40], 7.73°, 28.6° and 35.6° for ZnAl-[PW12O40], and 8.61°, 25.27°, 34.96° and 66.34° for ZnAl-[SiW12O40]. The materials were characterized as an advanced catalyst to improve photocatalytic activity for RhB elimination under visible light sources. The intercalation of polyoxometalate [SiW12O40]4- and [PW12O40]3- into LDH could enhance the degradation cationic dye of RhB. Intercalation improved the photodegradation performance determined under UV-Vis irradiation conditions which composite NiAl-LDH was better than ZnAl-LDH composite. It was present by the %degradation RhB performances NiAl-LDH, ZnAl-LDH, NiAl-[SiW12O40], NiAl-[PW12O40], ZnAl-[SiW12O40], and ZnAl-[PW12O40] were 91.48%, 88.59%, and 88.41%, and 87.87%, respectively. The %degradation for NiAl-LDH and ZnAl-LDH was 68.94% and 65.76%. Recovery and reusability experiment of the catalyst demonstrated by degradation percentage that the LDH intercalated polyoxometalate has a great photocatalytic ability.